WAYS TO FORM A MIDDLE CLASS OF OWNERS (World Bulletin of Management and Law, 2024)
In this article has been researched the social and economic significance of the formation of the middle class of owners and the factors that affect them.
Keywords: Property owner; denationalization; nongovernmental sector